Brachial plexopathy due to malignant peripheral nerve sheath tumor in neurofibromatosis type 1: Case report and subject review - Pacelli, James; Whitaker, Charles H. (Muscle & nerve, 2006)
Neurofibromatosis type 1 (NF1) is a common tumor predisposition syndrome affecting approximately 1 in 4,000 persons. It is an autosomal‐dominant disorder with half of the cases resulting from spontaneous mutations. This genetic defect leads to the formation of benign tumors or neurofibromas of the peripheral nervous system. Dermal neurofibromas may cause local discomfort and itching but are rarely associated with neurological deficit and do not undergo malignant change. The more extensive plexiform neurofibromas produce neurological complications in 27%–43% of patients with NF1 and may undergo malignant degeneration in 5% of cases. Patients with NF1 who develop pain or new neurological symptoms should have a rapid and thorough assessment for malignancy. In this report, we illustrate this point by presenting a patient who developed acute shoulder pain and weakness due to malignant degeneration of a plexiform neurofibroma involving the left brachial plexus, and review the literature on this subject. Muscle Nerve, 2006